Flowing suspensions of carbon black with high electronic conductivity for flow applications: Comparison between carbons black and exhibition of specific aggregation of carbon particles. (August 2017) - Parant, H.; Muller, G.; Le Mercier, T.; Tarascon, J.M.; Poulin, P.; Colin, A.
Abstract: Flow batteries and flow capacitors are promising technologies to store and generate electrical power. However, to increase their energy performances, low viscosity, electronic conductive suspensions loaded with active material are required. Comparing the behavior of three types of carbon black particles in water suspensions, we show that compressed acetylene carbon black particles suspensions display a slow variation of viscosity and conductivity as a function of concentration. It allows reaching intermediate viscosity (1 Pa s for a shear rate of 10 s −1 ) with high electronic conductivity between 0.1 and 5 mS/cm. This behavior is very promising for flow applications. At small range, attractive van der Walls interactions between carbon aggregates dominate. However, at longer range, compressed acetylene carbon black particles are highly attractive in water. After shearing with emulsifier, fractal-like shape clusters are obtained through a diffusion limited aggregation process. These fractal clusters constitute the building blocks of a flexible connected network. By contrast, for the two other investigated carbons, an energy barrier has to be overcome to enable aggregation. The clusters are compact and result from a reaction limited aggregation process. For these two carbons, the conductivity and the viscosity vary abruptly at percolation which is not suitable for flow devices. Graphical abstract: